2020
DOI: 10.3906/tar-1903-40
|View full text |Cite
|
Sign up to set email alerts
|

Application of handheld laser scanning technology for forest inventory purposes in the NE Turkey

Abstract: Forest inventory (FI) is the most challenging stage of forest management and planning process. Therefore, in situ surveys are often reinforced by modern remote sensing (RS) methods for collecting forestry-related data more efficiently. This study tests a stateof-the-art data collection method for practical use in the Turkish FI system for the first time. To this end, forest sampling plots were conventionally measured to collect dendrometric data from 437 trees in Artvin and Saçınka Forest Enterprises. Then, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 40 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…However, if data geolocation is not considered necessary, permanent plot establishment, like the one defined in Section 2.2 will still allow scan co-registration over time. Although this technology has been shown to provide rapid inventory of forest plots [29,57,58], its uptake by forest restoration ecologists for the monitoring of restoration plantings is still lagging. The present study demonstrates the potential of remote sensing technology, and particularly the ZEB1 system, to monitor the development of structural traits over time to guide adaptive management and report on restoration effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…However, if data geolocation is not considered necessary, permanent plot establishment, like the one defined in Section 2.2 will still allow scan co-registration over time. Although this technology has been shown to provide rapid inventory of forest plots [29,57,58], its uptake by forest restoration ecologists for the monitoring of restoration plantings is still lagging. The present study demonstrates the potential of remote sensing technology, and particularly the ZEB1 system, to monitor the development of structural traits over time to guide adaptive management and report on restoration effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Cabo et al [54] showed that the performance of ZEB-REVO-based dbh measurement (RMSE 0.9-1.1 cm) was equivalent to that of TLS; there was no apparent differences in tree detection nor significant bias in dbh estimation. Vatandaşlar and Zeybek [57] found that ZEB-REVO-collected 3D data yielded slightly higher dbh values than conventional ground measurements. However, its correlation coefficients ranged between 0.978 and 0.998.…”
Section: Introductionmentioning
confidence: 96%
“…Maybe in the future, these instruments will be suitable for measurements in forestry due to them being inexpensive and easy to use compared to equipment that is expensive, often heavy, and difficult to process. Lidar on an iPhone or tablet today uses the viDOC Pix4D system to create high-quality 3D models of smaller objects using the GNSS RTK module [43,44].…”
Section: Mobile Low-cost Systems (Smartphones and Tablets)mentioning
confidence: 99%
“…A better solution is a handheld scanner-a personal laser scanner (PLS). Nowadays, there is more suitable equipment, such as ZEB-REVO (GeoSlam, Nottingham, UK), BLK2go (Leica, Heerbrugg, Switzerland) (introduced in April 2020), or other devices [35,[41][42][43][44].…”
Section: Mls/plsmentioning
confidence: 99%